2015
DOI: 10.1002/ccd.26151
|View full text |Cite
|
Sign up to set email alerts
|

Management of drug eluting stent in‐stent restenosis: A systematic review and meta‐analysis

Abstract: Treatment of coronary DES ISR with DES or DEB is associated with a reduction in the risk of TLR and TVR compared to BA alone. The relative risk reduction for TLR with DES is similar to DEB. DEBs have a potential role in the treatment of DES ISR by avoiding placement of another layer of stent. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…Mamuti et al 29 showed no significant difference in MACE in BMS/DES ISR therapy using PEB versus PES/EES (RR, 1.04; P=0.80) as well. Goel et al 30 comparing the efficacy of DES, PEB, and POBA in the treatment of DES ISR suggested that DES and PEB seem to reduce the risk of TLR (OR, 0.50 and 0.31) and TVR (OR, 0.55 and 0.32) compared with POBA alone.…”
Section: Resultsmentioning
confidence: 99%
“…Mamuti et al 29 showed no significant difference in MACE in BMS/DES ISR therapy using PEB versus PES/EES (RR, 1.04; P=0.80) as well. Goel et al 30 comparing the efficacy of DES, PEB, and POBA in the treatment of DES ISR suggested that DES and PEB seem to reduce the risk of TLR (OR, 0.50 and 0.31) and TVR (OR, 0.55 and 0.32) compared with POBA alone.…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of patients with ISR continues to remain a challenge, and currently available options include angioplasty alone, repeat stenting with DES or drug-coated balloons (DCB). 6) Recent meta-analyses have performed comparisons of these available options in an attempt to identify the preferred therapeutic modality. Therefore, this review will discuss the currently available therapeutic strategies for the management of patients with ISR and the evidence supporting their use.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of coronary ISR with DES is associated with the lowest rate of TVR. Initial research suggested that drug‐eluting balloons and DES provided reasonable angiographic results among patients treated for coronary ISR . Several network meta‐analyses have confirmed these findings, suggesting that treatment with a DES was associated with lower rates of TVR compared to isolated balloon or scoring balloon angioplasty .…”
Section: Discussionmentioning
confidence: 97%